Design and Construction of Information System Ticket Ordering at Green Lake View Waterpark Depok - Widya Paslan (ENCRYPTION: Journal of Information And Technology, 2024)
This research stems from observations at Green Lake View Waterpark, a popular tourist destination often crowded on holidays and weekends. The study found that ticket ordering is still handled manually, requiring visitors to queue at the counter a process that leads to long waiting times and discomfort, especially during peak periods. This conventional system also poses challenges for management in tracking transactions, reporting, and monitoring visitor numbers in real time. To address these issues, the author proposes a digital-based ticket ordering information system. This system aims to allow visitors to purchase tickets independently and flexibly, reducing queues and improving the overall experience. Additionally, it would help management efficiently manage and monitor data. The proposed solution is expected to enhance service quality and operational efficiency at Green Lake View Waterpark.